Long-term results of multilevel surgery in adults with cerebral palsy - Putz, Cornelia; Erhard, Sarah; Fiethen, Katharina; Geisbüsch, Andreas; Thielen, Mirjam; Wolf, Sebastian Immanuel; Dreher, Thomas (International orthopaedics, 2019)
BackgroundDeterioration of gait in adolescent and adult patients with cerebral palsy can be associated with multiple factors. Multilevel surgery (MLS) is one option in adults with cerebral palsy to improve gait function with encouraging short-term results. It is a question whether these improvements are maintained over time.MethodsIn a retrospective consecutive cohort study, adults with bilateral spastic cerebral palsy (BSCP) treated with MLS between 1995 and 2011 were scanned for potential inclusion. Patients needed to fulfill the following inclusion criteria: age at MLS > 17, standardized three-dimensional gait analysis (3D-GA) including clinical examination at pre-operative (E0), a short-term follow-up (E1) and at least seven years (E2) after the index MLS. Twenty adults (10 women, 10 men) with a Gross Motor Function Classification Level (GMFCS) I-III and a mean age at MLS of 24.8 years were included in this study. The average long-term follow-up was 10.9 years. The Gait Profile Score (GPS) was used as primary outcome measure.ResultsThe GPS improved significantly from 13.8° before surgery to 11.2° at short-term (p = 0.007) and to 11.3° at long-term follow-up (p = 0.002). Mean GPS showed a slight deterioration between E1 and E2 due to a minority of six patients (30%) who showed a significant loss of correction.ConclusionSurgical treatment in adults with BSCP was feasible and effective in the long-term. Significant improvement of gait and function was maintained in the majority of patients, while some patients were prone to develop crouch gait, hip flexion contractures, or pain.